Flexible bronchoscopy for lung cancer diagnosis in patients aged ≥85 years. Issue 1 (16th November 2021) - Mineshita, Masamichi; Morikawa, Kei; Furuya, Naoki; Kida, Hirotaka; Nishine, Hiroki; Handa, Hiroshi; Inoue, Takeo
Abstract : Aim: Flexible bronchoscopy (FB) is a common modality for the diagnosis of lung cancer. Recently, the number of older patients with lung cancer is increasing, and FB is being utilized more for these patients. Methods: FB carried out in patients aged ≥85 years at St. Marianna University Hospital, Kawasaki, Japan, were reviewed. The indication of FB was decided on a case‐by‐case basis, taking into consideration the condition of the patient, which included mental status and accessibility of the lesion. Outcomes included complications, diagnostic yields, treatment options and survival after FB evaluation. Results: From April 2015 to March 2019, 1604 diagnostic FBs were carried out. A total of 28 were carried out for the diagnosis of lung cancer (19 transbronchial lung biopsy, 9 transbronchial needle aspiration) in patients aged ≥85 years. Although there were three complications reported (pneumonia, fever, asthma exacerbation), they were successfully treated. A total of 19 cases were diagnosed with malignancy; five were treated with stereotactic body radiation therapy, five were prescribed targeted therapy, two underwent surgery and one was treated by cytotoxic monotherapy. Six patients were not included for active treatment. A total of 12 patients who received active treatment for lung cancer reported a 2‐year survival rate of >60%. Conclusions: FB for lung cancer diagnosis in patients aged ≥85 years were carried out with acceptable safety and diagnostic yield. Considering the development of less invasive therapeutic measures for lung cancer, FB is safe and valuable in individuals aged ≥85 years suspected of lung cancer with therapeutic indications. Geriatr Gerontol Int 2022; 22: 32–35 .